Antihistaminergic and Anticholinergic Properties of the Root Bark Aqueous Extract of Diospyros mespiliformis (Ebenaceae) on Hypersecretion of Gastric Acid Induced in Wistar Rats. (31st January 2022) - Vandi, Vandza Luc; Amang, André Perfusion; Mezui, Christophe; Siwe, Gaël Tchokomeni; Ndji, Gustave Lebeau Otto; Mbida, Hacheked; Baponwa, Odile; Tan, Paul Vernyuy
Abstract : Objective . The objective of this study was to elucidate the antisecretory mechanism of the root bark aqueous extract of Diospyros mespiliformis (RBAEDM) in Wistar rats. Materials and methods . RBAEDM was tested on three experimental animal models of gastric acid hypersecretion including pyloric ligation (PL), PL with histamine, and carbachol pretreatments. The ulcerated surface, mucus mass, pH, gastric acidity, and pepsin activity were determined. Some bioactive compounds revealed by qualitative phytochemistry were quantified. Some markers of oxidative stress in vivo such as malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), and in vitro antioxidant tests (ABTS: 2, 2′-azinobis-3-ethylbenzothiazoline-6-sulfonic acid, DPPH: 2, 2-diphenyl-2-picrylhydrazyl, and FRAP: ferric reducing antioxidant power) were determined. Results . In the three models studied, RBAEDM resulted in increases in the percentages of inhibition ranging from 9.50 to 59.52% of gastric ulcer and mucus mass. This increase was accompanied by the reduction in acidity and pepsin activity. The administration of RBAEDM resulted in a significant decrease (p < 0.05, p < 0.01 ) in MDA levels correlated with a significant increase (p < 0.05, p < 0.01 ) in CAT and nitrite levels compared with the negative control. RBAEDM has the ability to scavenge ABTS and DPPH radicals and to reduce FRAP, and the inhibitory concentration of 50% (IC50 ) of the ABTS radical was 220  μ g/mL compared with the butylhydroxytoluene (BHT) control (175  μ g/mL). Quantitative phytochemistry revealed abundant polyphenols, flavonoids, tannins, saponins, and anthocyanin. Conclusion . RBAEDM protected gastric mucous membrane for gastric acid by mechanisms that would involve both anticholinergic and antihistaminergic pathways.